2012
DOI: 10.1590/s0102-695x2012005000048
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anticonvulsant activity of ethanolic leaves extract of Desmodium triflorum in mice

Abstract: The present investigation was aimed to study an anticonvulsant activity of ethanolic extract of Desmodium triflorum (L.) DC., Fabaceae, in mice. Animal models of epilepsy namely the pentylenetetrazole (PTZ), isoniazid or isonicotinic hydrazide (INH) and maximal electroshock induced convulsion (MES) were used to evaluate the anticonvulsant effects of the extracts. The biochemical estimation was done by measuring the lipid peroxidation and reduced glutathione (GSH). In the PTZ induced convulsion, ethanolic extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…This model is acute model of seizures. Various studies using MES and PTZ induced seizures did not report effect of male and female animals on seizures severity [ [19] , [20] , [21] , [22] ]. Similar results were observed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…This model is acute model of seizures. Various studies using MES and PTZ induced seizures did not report effect of male and female animals on seizures severity [ [19] , [20] , [21] , [22] ]. Similar results were observed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…The enhancement of the GABAergic neurotransmission is reported to antagonize seizures, while the inhibition of the neurotransmission boosts seizures. The protection of mice against PTZ-induced seizures by the standard anticonvulsant drugs, phenobarbitone and diazepam is expected since many authors have demonstrated that they describe their anticonvulsant activities by increasing GABA-mediated inhibition 40 .…”
Section: Clerodendrum Infortunatummentioning
confidence: 99%
“…About 75-80% of the world's population and especially of the developing countries uses medicinal plants for the treatment of epilepsy because of better compatibility with the human body and lesser side effects [6]. Actually, medicinal plants to be an important source of traditional medicines to treat epilepsy.…”
Section: Introductionmentioning
confidence: 99%